Factors Influencing Mutual Fund Investment Decisions: Insights from Women Investors - Prajapati, Nabin; Swongamikha, Jyoti (Bagiswori Journal, 2024)
With the economic transformations and wider access to financial knowledge, the capital market is witnessing a surge in female investors. Among the various investment options available in the market, mutual funds are one of the major options that are known to provide greater returns compared to the traditional investments. This study has been carried out with the objectives of studying mutual fund investment decisions from the perspective of women investors in Nepal. It identifies different factors that affect the investment decision of women investors in Nepal. Basically, this study adopts descriptive research design to describe and measure the data whereas causal comparative research design is used to analyze the impact of specific factors on mutual fund investment decisions of women investors. Meanwhile the study showed that different factors such as financial and accounting information, investors’ consultation with advisors and the image of mutual fund issuing companies have a positive significant influence in the investment decision of women in Nepal. Unlikely the study showed insignificant effect of investment knowledge of investors and general economic condition on the investment decision of women investors. This study can lay the groundwork for effective educational programs and policy changes that enables women investors to make financial decisions and promote equitable practices in the financial investment sector.